2007
DOI: 10.1021/jo0703698
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Terpene and Steroid Dimers and Trimers Having Cyclobutadienyl−Co and Aromatic Tethers

Abstract: The reaction of natural product derived propargylic alcohols with CpCo(CO)2 produces three new types of natural product hybrids having two or three terpene or steroid fragments. The tether joining the natural product subunits is built during the reaction. Type 1 hybrids have two terpene or steroid moieties joined by a CpCo-cyclobutadiene tether, with the two units disposed in a 1,2-arrangement (9, 14, 22). Type 2 hybrids have a Co-cyclopentadienone tether (10). Type 3 has three units of terpene or steroid join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…It is interesting to note that easily enolizable aldehydes (alkyl aldehydes C 3 -C 5 ) produced alkynylated products 3a-e with 95-98% yields and no aldol condensation by products were formed. Benzaldehyde derivatives having both electron-donating and withdrawing substituents, 2-naphthaldehyde, and a heterocyclic aldehyde gave the products in good to excellent yields (entries [6][7][8][9][10][11][12][13][14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that easily enolizable aldehydes (alkyl aldehydes C 3 -C 5 ) produced alkynylated products 3a-e with 95-98% yields and no aldol condensation by products were formed. Benzaldehyde derivatives having both electron-donating and withdrawing substituents, 2-naphthaldehyde, and a heterocyclic aldehyde gave the products in good to excellent yields (entries [6][7][8][9][10][11][12][13][14].…”
Section: Resultsmentioning
confidence: 99%
“…The alkynylation of carbonyl compounds is a direct chain extension reaction. [1][2][3][4][5][6][7][8] Propargylic alcohols are important and versatile building blocks for many biologically active compounds and natural products such as adociacetylene B, 9 longimicin D, 10 leukotriene B 4 , 11 steroid, 12 prostaglandins, 13 and carotenoids, 14 and have gained considerable attention in recent years. The most common methods to obtain propargylic alcohols are the nucleophilic addition of stoichiometric amounts of strong bases such as organolithium, dialkyl zinc or organomagnesium reagents with or without Lewis acids.…”
Section: Introductionmentioning
confidence: 99%
“…Sierra et al described the homocyclotrimerization of mestranol into the corresponding 1,2,4-trisubstituted benzene derivative in the presence of an excess of CpCo(CO) 2 under harsh conditions. [39] Later, Kotora et al showed that 32 easily underwent intermolecular [2+2+2] cycloadditions with various diynes, catalyzed by Wilkinson's complex -[Rh(PPh 3 ) 3 Cl] -under mild conditions to provide the corresponding 17α-arylestradiols 33 (Scheme 12) in good yields. [40] The prepared compounds were tested as selective ligands for estrogen receptor β.…”
Section: The Heck Reaction and Cross-coupling Proceduresmentioning
confidence: 99%
“…Propargyl alcohol is a valuable building block and an important chemical intermediate in the synthesis of complex natural products with significant biological activity and other useful materials . In addition, propargyl alcohol has been widely used as corrosion inhibitors in steel industries .…”
Section: Introductionmentioning
confidence: 99%